Workshop Perancangan Modul Ajar dan Asesmen Pembelajaran Menggunakan Artificial Intelligence - Firdiani, Dian; Pratiwi, Andi Citra; Khalidatunnisa, Besse; Daud, Firdaus; Mar'ah, Zakiyah (Program Studi Manajemen FEB UNM, 2025)
This community service activity aims to enhance teachers' capacity in designing instructional modules and learning assessments based on the Merdeka Curriculum by utilizing artificial intelligence (AI) technology. The background of this activity stems from the need for teachers to develop adaptive and meaningful learning experiences that align with students’ characteristics, especially in response to the challenges of digital transformation in education. The activity was conducted in the form of a participatory workshop involving elementary school teachers from the Manuju District, Gowa Regency, as participants. The implementation methods included a preliminary study, needs identification, hands-on practice in developing AI-based teaching modules and assessments, as well as reflective discussions. The results of the activity indicate that participants experienced improved understanding of the principles of the Merdeka Curriculum and enhanced technical skills in using various AI platforms to design more effective and efficient lesson plans. The workshop also contributed positively to raising teachers’ awareness of the importance of utilizing technology to support the development of the Pancasila Student Profile. Overall, this community service activity demonstrates that the integration of technology into instructional planning holds significant potential for improving the quality of both the educational process and outcomes.